Molecular basis of TRPA1 regulation in nociceptive neurons. A review - Kádková, Anna; Synytsya, Viktor; Krůšek, Jan; Zímová, Lucie; Vlachová, Viktorie (Physiological research, 2017)
Transient receptor potential A1 (TRPA1) is an excitatory ion channel that functions as a cellular sensor, detecting a wide range of proalgesic agents such as environmental irritants and endogenous products of inflammation and oxidative stress. Topical application of TRPA1 agonists produces an acute nociceptive response through peripheral release of neuropeptides, purines and other transmitters from activated sensory nerve endings. This, in turn, further regulates TRPA1 activity downstream of G-protein and phospholipase C-coupled signaling cascades. Despite the important physiological relevance of such regulation leading to nociceptor sensitization and consequent pain hypersensitivity, the specific domains through which TRPA1 undergoes post-translational modifications that affect its activation properties are yet to be determined at a molecular level. This review aims at providing an account of our current knowledge on molecular basis of regulation by neuronal inflammatory signaling pathways that converge on the TRPA1 channel protein and through modification of its specific residues influence the extent to which this channel may contribute to pain.
Keywords: signální transdukce; Nociceptors; Animals; Signal Transduction; Humans; lidé; bradykinin; Pain; Bradykinin; zvířata; TRPA1 Cation Channel; nociceptory; bolest; kationtový kanál TRPA1